Echolalia: Paying attention to a forgotten clinical feature of primary progressive aphasia. - Torres-Prioris, María José; Berthier-Torres, Marcelo Luis (Wiley, 2021)
Primary progressive aphasia (PPA) variants—nonfluent-agrammatic (nfvPPA), semantic (svPPA), and logopenic (lvPPA)—exhibit diverse language impairments, with echolalia (verbal repetition) underexplored. Echolalia arises from disrupted speech-language network (PSLN) dynamics, impaired in nfvPPA and lvPPA but relatively preserved in svPPA and behavioral variant frontotemporal dementia (bvFTD). Ota et al. studied echolalia in 45 PPA patients, identifying it in 12 nfvPPA and 2 unclassified cases. Echolalia in nfvPPA was associated with younger age, impaired auditory comprehension, and preserved repetition akin to transcortical aphasias, challenging traditional diagnostic tools like the Western Aphasia Battery. Mitigated echolalia was the predominant form, linked to faulty comprehension and inhibitory control. Potential echolalia in svPPA was underestimated, as repetitive questioning was excluded. No echolalia was reported in lvPPA, likely due to methodological limitations. Functional imaging linked echolalia in nfvPPA to reduced activity in executive-control regions, triggering automatic PSLN activation. These findings underscore the need for further studies to clarify echolalia's diagnostic significance in PPA variants.
https://openpolicyfinder.jisc.ac.uk/id/publication/7713
Keywords: Dementia; Echolalia; Primary rogresive aphasia